2008
DOI: 10.1007/s00424-008-0579-1
|View full text |Cite
|
Sign up to set email alerts
|

Defective jejunal and colonic salt absorption and alteredNa+/H+ exchanger 3 (NHE3) activity in NHE regulatory factor 1 (NHERF1) adaptor protein-deficient mice

Abstract: We investigated the role of the Na+/H+ exchanger regulatory factor 1 (NHERF1) on intestinal salt and water absorption, brush border membrane (BBM) morphology, and on the NHE3 mRNA expression, protein abundance, and transport activity in the murine intestine. NHERF1-deficient mice displayed reduced jejunal fluid absorption in vivo, as well as an attenuated in vitro Na+ absorption in isolated jejunal and colonic, but not of ileal, mucosa. However, cAMP-mediated inhibition of both parameters remained intact. Acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 37 publications
3
74
1
1
Order By: Relevance
“…We observed a 31% increase in NHE3 activity in Nherf1 -/-mice compared with a 47% increase in WT mice, indicating that NHE3 regulation by chronic insulin treatment is partially dependent on transcriptional/translational activation of NHE3 (Supplemental Figure 3). However, the basal NHE3 activity was reduced in Nherf1 -/-mice, as previously reported (17), which therein indicates that NHE3 activity in Nherf1 -/-mice after 5 days of insulin treatment was significantly lower compared with that of WT mice.…”
Section: Nhe3 Activity and Fluid Absorption Are Decreased In The Intesupporting
confidence: 89%
See 1 more Smart Citation
“…We observed a 31% increase in NHE3 activity in Nherf1 -/-mice compared with a 47% increase in WT mice, indicating that NHE3 regulation by chronic insulin treatment is partially dependent on transcriptional/translational activation of NHE3 (Supplemental Figure 3). However, the basal NHE3 activity was reduced in Nherf1 -/-mice, as previously reported (17), which therein indicates that NHE3 activity in Nherf1 -/-mice after 5 days of insulin treatment was significantly lower compared with that of WT mice.…”
Section: Nhe3 Activity and Fluid Absorption Are Decreased In The Intesupporting
confidence: 89%
“…The changes in the expression of NHERF1 and NHERF2 but not NHERF3 were reversed by insulin. It has been shown that basal NHE3 activity is reduced in Nherf1 -/-or Nherf3 -/-mouse intestines (17,37), suggesting that NHERF1 and NHERF3 may be involved in the basal expression of NHE3 at the plasma membrane. Loss of NHERF1 in mice or knockdown of NHERF1 in Caco-2bbe cells ablated insulin-mediated NHE3 activation, indicating that NHERF1 is indispensable for NHE3 regulation.…”
Section: Activation Of Nhe3 By Insulin Requires the Assembly Of Ezrinmentioning
confidence: 99%
“…NHERF1 Ϫ/Ϫ mice featured reduced jejunal fluid absorption in vivo, as well as attenuated in vitro Na ϩ absorption in isolated jejunal and colonic, but not ileal, mucosa. Moreover, NHE3 activity and membrane expression were reduced, although mRNA levels were not affected (21). One study found NHERF2 Ϫ/Ϫ mice to have lower ileal NHE3 activity due to impaired trafficking or retention of NHE3 in the apical membrane (99), which is possibly related to NHERF2 association with lipid-raft NHE3 (136).…”
Section: Healthy Intestinal Tract Epitheliummentioning
confidence: 99%
“…1). A direct implication of this decrease in NHE3 activity is a lower Na ϩ absorption [with highest impact in the proximal colon, where electroneutral NaCl uptake is more relevant (122)], which in turn contributes to the IBD-associated diarrhea (21,43,135,156). Some studies reported both lowered activity and expression of NHE3 (13,125,135), whereas others have observed reduced NHE3 activity associated with no changes in expression (43,85,156,157).…”
Section: Nhe3 Is Impaired In Ibdmentioning
confidence: 99%
“…In the gastrointestinal tract, the sodium/hydrogen exchanger isoform 3 (NHE3) plays an important role in sodium and fluid homeostasis (11)(12)(13). Tenapanor (AZD1722 and RDX5791) is a small molecule inhibitor of NHE3 being developed for the treatment of patients with CKD.…”
Section: Introductionmentioning
confidence: 99%